Access to Finance as a Mediator of The Relationship Between Financial Literacy and Financial Technology on MSMEs Sustainability - Arienda Gitty Ramadani; Ferawati; Dewi Khornida Marheni (Jurnal Manajerial, 2025)
Background - Micro, Small, and Medium Enterprises (MSMEs) are crucial for driving Indonesia's economic growth. However, their sustainability often faces challenges due to limited access to financial resources and minimal use of financial technology. Many MSMEs also exhibit low financial literacy, which impacts their ability to manage their finances efficiently and utilize digital financial instruments. In an increasingly complex and competitive market landscape, the ability of MSMEs to obtain funding and utilize financial technology is crucial for achieving sustainable growth. Objective - This study aims to examine the mediating effect of access to finance on the relationship between financial literacy and financial technology on the sustainability of MSMEs. This study specifically examines whether financial literacy and financial technology can have a significant impact on the sustainability of MSMEs, both directly and indirectly through access to finance as a mediating factor. Design/Methodology/Approach - This study employed a quantitative methodology using a questionnaire to collect data from 150 MSME participants in Batam City. The sampling technique used was purposive sampling, specifically aimed at financial technology users. Data were collected through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS software. This model combines reliability, validity, and significance assessments through bootstrapping to evaluate direct and indirect influences between variables. Find - The findings of this study indicate that financial technology significantly influences the sustainability of MSMEs, both through direct connections and through a mediation process through access to finance. Access to finance has been shown to significantly influence the sustainability of MSMEs. Conversely, financial literacy does not show a significant direct impact on sustainability, nor does it have a significant indirect effect through access to finance. These findings emphasize that the influence of financial technology is greater than financial literacy in increasing the competitiveness and sustainability of MSMEs in today's digital era. Conclusion - The conclusion obtained in this study is that financial literacy does not have a significant direct influence on the sustainability of MSMEs. In contrast, financial technology and access to finance have a significant positive influence on the sustainability of MSMEs. Access to finance mediates the relationship between financial technology and MSME sustainability, but access to finance does not mediate the relationship between financial literacy and MSME sustainability. This finding confirms the importance of adopting financial technology in strengthening the sustainability of MSMEs. Research Implications - The findings of this study provide important insights for various parties, particularly the government, financial institutions, and business support service providers. They need to be more proactive in encouraging the use of financial technology among MSMEs to support business closures. Furthermore, financial literacy programs need to be designed with a more applicable approach and be relevant to the needs of MSMEs, particularly those related to the use of digital financial services, so that their benefits are truly felt in daily business practices. Limitations - This study has several limitations. It is geographically confined to Batam City, limiting the generalizability of its findings to other regions in Indonesia. Furthermore, as a purely quantitative study, it does not explore in-depth behavioral or socio-psychological factors that may influence MSME sustainability. Future research is recommended to employ a mixed-methods approach and expand the scope to other regions to gain more comprehensive insights.